Editorial: Introduction to the special issue on teaching English reading and writing to young learners - Reynolds, Barry Lee; Teng, Mark Feng (Studies in Second Language Learning and Teaching, 2021)
We aimed for this special issue to offer up empirically supported advice to teachers for tackling some of the challenges in teaching reading and writing to young English as a second (L2) or foreign language (FL) learners. These challenges teachers face when providing instruction to young learners include cognitive development, motivation, attention, strategy use, and assessment (Nunan, 2011). It is now well understood that the teaching of reading and writing to young learners can no longer be equated with the teaching of adult learners (Cameron, 2001). In terms of cognitive development, language learners need to go through significant developmental changes in their learning journey from infancy to adulthood (Richardson, 2019). These differences in language learners’ cognitive development call for a need to design language learning tasks and materials that can fit the developmental stages of learners (Teng, 2020a). Language learner motivation can decline over time due to a lack of clarity in the goals of language learning and potential feelings that effort invested in learning the language has not paid off (Linse & Nunan, 2006). Furthermore, as young learners tend to have short attention spans, activities that can maintain their motivation and involvement are essential (Fenyvesi, 2020). Language learning strategy researchers have focused their attention on adult learners; however, we believe they should begin considering young learners’ language use and learning preferences, as this knowledge could help inform teachers’ instruction (Plonsky, 2019). To provide proper instruction, an educator of young learners must understand these needs. This requires the construction of appropriate language assessment tools, which will allow teachers to gauge learners’ strengths and weaknesses; doing so can further facilitate teacher scaffolding and other forms of feedback (Ma & Bui, this issue). Despite the acknowledged impact that these issues have on the teaching of reading and writing to young learners, we are still lacking in empirical evidence to support many creative and pedagogical decisions made in the young learner classroom (Cameron & McKay, 2010). Our intention in this special issue was to further focus language researchers’ attention on the young learner classroom and to encourage a rethinking of classroom practices for teaching reading and writing.